Embedding knowledge in 3d data frameworks in cultural heritage - Flores Gutirrez, M.; Coughenour, C. M.; Lopez-Menchero Bendicho, V. M.; Fritsch, D.; De Kramer, M.; Ioannides, Marinos; Senecal, S.; Vincent, M. L. (My University, 2015)
At present, where 3D modeling and visualisation in cultural heritage are concerned, an object's documentation lacks its interconnected memory provided by multidisciplinary examination and linked data. As the layers of paint, wood, and brick recount a structure's physical properties, the intangible, such as the forms of worship through song, dance, burning incense, and oral traditions, contributes to the greater story of its cultural heritage import. Furthermore, as an object or structure evolves through time, external political, religious, or environmental forces can affect it as well. As tangible and intangible entities associated with the structure transform, its narrative becomes dynamic and difficult to easily record. The Initial Training Network for Digital Cultural Heritage (ITN-DCH), a Marie Curie Actions project under the EU 7th Framework Programme, seeks to challenge this complexity by developing a novel methodology capable of offering such a holistic framework. With the integration of digitisation, conservation, linked data, and retrieval systems for DCH, the nature of investigation and dissemination will be augmented significantly. Examples of utilisating and evaluating this framework will range from a UNESCOWorld Heritage site, the Byzantine church of Panagia Forviotissa Asinou in the Troodos Mountains of Cyprus, to various religious icons and a monument located at the Monastery of Saint Neophytos. The application of this effort to the Asinou church, representing the first case study of the ITN-DCH project, is used as a template example in order to assess the technical challenges involved in the creation of such a framework.
Keywords: 3D; Data integration; Digital cultural heritage; Photogrammetry